Administrative Reform Requirements and Their Impact on Sustainable Administrative Development: A Field Study at the Faculty of Technical Sciences in Misrata - Abdul Hakim Rajab Al-Nuairi; Muhammad Ali Muailif (Journal of Scientific and Human Dimensions, 2026)
This study aimed to analyze the impact of administrative reform requirements (transparency, oversight, environment, legislation, training, and digital transformation) on achieving sustainable administrative development in the Faculty of Technical Sciences. The results indicated that legislation and digital transformation significantly impact sustainable development, highlighting the importance of updating legal frameworks and activating digital transformation to enhance institutional efficiency and achieve strategic objectives. Other dimensions, such as transparency, oversight, environment, and training, did not show statistically significant effects in the current model. The Variance Inflation Factor (VIF) analysis revealed moderate to high multicollinearity, particularly between the environment and legislation variables, necessitating the use of advanced statistical techniques to ensure result accuracy. The study concluded by emphasizing the prioritization of legislation and digital transformation as fundamental elements of administrative reform while reconsidering strategies to enhance other dimensions. Recommendations were provided to improve transparency, oversight, and workplace environment to ensure sustainable administrative development.
Keywords: Administrative Reform; Characteristics of Administrative Reform; Transparency; Administrative Oversight; Digital Transformation; Sustainable Development